2003
DOI: 10.1002/chem.200304754
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene–BODIPY Cassettes: Syntheses and Energy Transfer

Abstract: Compounds based on the 4,4-difluoro-1,3,5,7-tetramethyl-4-bora-3a,4a-diaza-s-indacene (BODIPY) framework are excellent fluorescent markers. When BODIPY dyes of this type are conjugated to functionalities that absorb at relatively short wavelengths, those functionalities can, in some molecules, transmit the absorbed energy to the BODIPY which then fluoresces. In such cases the BODIPY fragment acts as an acceptor while the other group serves as a donor. Energy transfer efficiencies in such donor-acceptor cassett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
204
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(224 citation statements)
references
References 44 publications
13
204
1
6
Order By: Relevance
“…These shortcomings normally require alternative photophysical designs such as antenna-Bodipy energy transfer dyads. [44][45][46][47] …”
Section: Uv/vis Absorption and Fluorescence Propertiesmentioning
confidence: 99%
“…These shortcomings normally require alternative photophysical designs such as antenna-Bodipy energy transfer dyads. [44][45][46][47] …”
Section: Uv/vis Absorption and Fluorescence Propertiesmentioning
confidence: 99%
“…36 BODIPY chromophores have also been used in synthetic light-harvesting antenna, 37 photonic wires, 38 optoelectronic gates, 39 and other energy donor-acceptor systems. [40][41][42] Photoinduced ET reactions with BODIPY dyes have already been reported. Tonimura et al have shown that the fluorescence of BODIPY dyes can be efficiently quenched by nucleotide bases.…”
Section: Introductionmentioning
confidence: 99%
“…The bodipy moiety is well known as an efficient through-bond energy acceptor for anthracene. [10] Herein, we present the first evidence of a uniquely spinpolarized quartet photoexcited state generated by a novel spin-polarization mechanism via the ion-pair state. Compound 1 was synthesized according to Scheme 1.…”
mentioning
confidence: 97%
“…As a model compound, we designed 1, in which a 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (bodipy) acceptor moiety (A), [10] is covalently linked through an anthracene moiety, as a donor (D) to the verdazyl p radical (R). p-Conjugated system 2 (D-R) has a quartet (S = 3/2) photoexcited state.…”
mentioning
confidence: 99%
See 1 more Smart Citation